Long‐term prognosis of Japanese Lambert–Eaton myasthenic syndrome patients with or without small‐cell lung carcinoma. Issue 2 (20th April 2020) - Kojima, Yuta; Uzawa, Akiyuki; Shibuya, Kazumoto; Yasuda, Manato; Ozawa, Yukiko; Oda, Fumiko; Shiraishi, Hirokazu; Motomura, Masakatsu; Kuwabara, Satoshi
Abstract: Objective: Lambert–Eaton myasthenic syndrome (LEMS) is a paraneoplastic neurological syndrome, most frequently associated with small‐cell lung carcinoma (SCLC). The survival of LEMS patients depends on the presence of SCLC, whereas the functional outcome in patients without SCLC has not been fully clarified. The aim of this study was to elucidate the long‐term prognosis of LEMS patients with or without SCLC. Methods: We collected data from seven consecutive Japanese patients with LEMS without SCLC ( n  = 4) or LEMS with SCLC ( n  = 3) consulting Chiba university hospital, Chiba, Japan from 2003 to 2019. The functional disability was assessed with the modified Rankin Scale. Results: The median observation period was 52 months (range 18–168 months); one LEMS with SCLC patient died as a result of SCLC 18 months after diagnosis, whereas the remaining two LEMS with SCLC patients with complete remission of their tumor still showed improvement in neurological symptoms 52 and 168 months after treatment, respectively. All LEMS patients without SCLC showed a favorable response to treatment and good functional prognosis (modified Rankin Scale 1 or 2) during the follow‐up period (48–120 months). Conclusions: In Japanese LEMS patients, the long‐term neurological outcome is generally favorable. Our results also suggest that even in LEMS with SCLC patients, successful treatment for their cancer could result in sustained improvement in neurological symptoms. Abstract : The aim of this study was to elucidate long‐term prognosis in Lambert–Eaton myasthenic syndrome. In Japanese Lambert–Eaton myasthenic syndrome patients, long‐term neurological outcome is generally good. Our results suggest that even in those with Lambert–Eaton myasthenic syndrome with small‐cell lung carcinoma, successful treatment for their cancer could result in sustained neurological remission.